U.S. Army counterinsurgency warrior handbook (Lyons Press, an imprint of Rowman & Littlefield, 2014)
Enter the U.S. Army Counterinsurgency Warrior Handbook, the counterinsurgency playbook used by the greatest army in the world. This manual establishes fundamental principles for tactical counterinsurgency operations at the company, battalion, and brigade levels. It is based on lessons learned from historic counterinsurgencies and current operations.